Efektivitas Pelatihan Kepemimpinan dalam Mengurangi Distres Kerja - Rifa Juniartika; Purwanti Endah Rahayu; Sabrina Etika Utami; Isna Asyri Syahrina; Annisa Fikri Sovia Ahmad (Psychopolytan : Jurnal Psikologi, 2026)
High demands within the modern public service sector frequently trigger occupational distress, negatively impacting employee mental health. This study aims to evaluate the effectiveness of leadership training in reducing psychological distress, specifically across the dimensions of depression, anxiety, and stress. Adopting a quantitative approach with a quasi-experimental one-group pre-test post-test design, the study involved 55 public service employees. The Depression Anxiety Stress Scales (DASS-42) was utilized to measure psychological conditions before and after the intervention. Data were analyzed using paired samples t-tests. The results indicated a statistically significant decrease in all three dimensions: depression (p=0.010), anxiety (p=0.003), and stress (p=0.006), with the stress dimension showing the most substantial reduction. These findings conclude that leadership training interventions are effective in mitigating work distress and can serve as a preventive strategy to enhance psychological well-being within organizational environments. Supportive leadership quality is proven to be a vital resource for employees in managing workplace pressure.